New Therapies for Advanced Thyroid Cancer - Laha, Diprajan; Nilubol, Naris; Boufraqech, Myriem (Frontiers in Endocrinology, 2020)
Despite the significant advances and discoveries in understanding the molecular pathogenesis of thyroid cancer, effective therapeutic strategies for advanced and metastatic, iodine-refractory thyroid cancer are still lacking. Here, we aim to discuss the most recent targeted therapies and immunotherapy for advanced thyroid cancer with a promising anti-tumor activity and clinical benefit.